LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK DISKUSI TERHADAP PERENCANAAN KARIR SISWA KELAS XII SMAN 1 SINDANGKERTA - farida, nada; Sekar Ayu Ningrum, Devy (IKIP Siliwangi, 2024)
This study aims to determine the success rate of group guidance services with discussion techniques on student career planning which refers to the phenomenon of students who are still confused in determining further education and lack understanding of the world of work. The variables in this study are career planning (Super, 1980) and group discussions (Romlah, 2020). Career planning according to Super (1980) is an individual thought process in seeking information and self-understanding as well as various aspects of work. This research method is Mix Methods using The Explanatory Sequential Design with One Group Pretest-Posttest Design. The subjects in this study were class XII students of SMAN 1 Sindangkerta with a population of 206 students. The research sample consisted of 8 students. This sampling technique uses a purvosive sampling technique according to Sugiyono (2019) explaining that the purposive sampling technique is a sample selection technique with certain considerations. The measuring instrument in this study used a student career planning scale with a reliability of 0.847. Based on the results of the Paired t-test worth 0.000 <0.05, it shows that the hypothesis Ho is rejected and Ha is accepted, which means that the guidance group with discussion techniques influences career planning for class XII SMAN 1 Sindangkerta so that it can be interpreted that the guidance group with discussion techniques can help improve the career planning of class XII students at SMAN 1 Sindangkerta.